In the Name of Civilisation. Sonja Schillings's Enemies of All Humankind. Fictions of Legitimate Violence (KULT_online, 2017)
Sonja Schillings's Enemies of All Humankind. Fictions of Legitimate Violence was published as part of a Dartmouth Series in American Studies, dedicated to tracing the United States’ participation in (as opposed to its domination of/disinterest from) global processes. Hence, Schillings’ investigation into the enemy-of-all-humankind set of figures (which she frames as “a constellation”) encompasses both transatlantic and interdisciplinary sources. Such a broad perspective allows the author to elucidate the role of the constellation in sustaining the othering discourses in the Anglo-American civilizational narrative. From corsairs of Algiers to G.I.s in Lahore, the author collects and scrutinizes a vast body of literature on the hostis humani generis constellation’s spatial, narrative, legal, and philosophical formulations. The development of the constellation – from Augustine of Hippo through Frederick James Turner to Giorgio Agamben – provides an opportunity to revisit classical and critical literary narratives of legitimate violence against hostis humani generis.